Efficient Multiplex Genome Editing Induces Precise, and Self-Ligated Type Mutations in Tomato Plants - Hashimoto, Ryosuke; Ueta, Risa; Abe, Chihiro; Osakabe, Yuriko; Osakabe, Keishi (Frontiers in Plant Science, 2018)
Several expression systems for multiple gRNAs have been developed in the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR associated protein 9) system to induce multiple-gene modifications in plants. Here, we evaluated mutation efficiencies in the tomato genome using multiplex CRISPR/Cas9 vectors consisting of various Cas9 expression promoters with multiple gRNA expression combinations. In transgenic tomato calli induced with these vectors, mutation patterns varied depending on the promoters used to express Cas9. By using the tomato ELONGATION FACTOR-1α (SlEF1α) promoter to drive Cas9, occurrence of various types of mutations with high efficiency was detected in the tomato genome. Furthermore, sequence analysis showed that the majority of mutations using the multiplex system with the SlEF1α promoter corresponded to specific mutation pattern of deletions produced by self-ligation at two target sites of CRISPR/Cas9 with low mosaic mutations. These results suggest that optimizing the Cas9 expression promoter used in CRISPR/Cas9-mediated mutation improves multiplex genome editing, and could be used effectively to disrupt functional domains precisely in the tomato genome.